RFID 시스템에서 Hash-Chain기반 Tag-Grouping을 이용한 안전하고 효율적인 데이터베이스 검색 - 이병주(Byeung-Ju Lee); 송창우(Chang-Woo Song); 정경용(Kyung-Yong Chung); 임기욱(Kee-Wook Rim); 이정현(Jung-Hyun Lee) (한국콘텐츠학회 논문지, 9(9), 2009)
RFID (Radio Frequency Identification) is a next generation technology that will replace barcode. RFID can identify an object by reading ID inside a RFID tag using radio frequency. However, because a RFID tag replies its unique ID to the request of any reader through wireless communication, it is vulnerable to attacks on security or privacy through wiretapping or an illegal reader's request. The RFID authentication protocol has been studied actively in order to solve security and privacy problems, and is used also in tag search. Recently, as the number of tags is increasing in RFTD systems and the cost of data collection is also rising, the importance of effective tag search is increasing. This study proposed an efficient search method that solved through ta9 group the problem of large volume of database computation in Miyako Ohkubo's hash chain mechanism, which meets requirements for security and privacy protection. When we searched first the group of tags with access rate of 5 or higher in a database with 100,000 records, search time decreased by around 30%. RFID(Radion Frequency Identification)는 바코드를 대체할 차세대 기술이다. RFID는 무선 주파수를 사용하여 RFID 태그 내부에 있는 ID를 읽어 물체를 식별할 수 있다. 하지만 RFID 태그는 어떤 리더의 요청에도 자신의 고유 ID를 무선 통신으로 응답하기 때문에 도청이나 불법 리더로부터 보안이나 프라이버시에 대한 공격에 취약하다. RFID 인증 프로토콜은 보안과 프라이버시 문제를 해결하기 위해 활발히 연구되고 있으며 태그 검색에도 사용되고 있다. 최근에는 RFID 시스템에서 태그의 수가 증가하고 데이터 수집 비용도 늘어나면서 효과적인 태그 검색에 대한 비중이 더 많아졌다. 본 논문에서는 보안과 프라이버시 보호를 위한 필요조건을 보장하는 Miyako Ohkubo의 hash-chain 메커니즘에서 데이터베이스 연산량이 많은 문제점을 Tag-Grouping을 통해 보완한 효율적인 검색 방법을 제안한다. 실험 결과 데이터베이스에서 10만개의 레코드 수를 기준으로 접근비율이 5이상인 태그 그룹의 우선 검색시 약 30%의 검색시간이 감소 하였다.